Teaching Physical Education using Alternative Practical Methods before Demonstration: Implication to Physical Education Specialists - Simon, Kayit Bobai; Adewole, Rufus Sunday; Muktar, Sa'adatu (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
The paper is on Implications of Teaching Physical Education by â€œAlternative to Practicalsâ€ method before demonstration: to the physical education specialist. The paper discussed the importance of teaching physical education in the development of the totality of the human being. This is the aspect of the teaching of the practical lessons to children of the young by the specialist. The paper revealed how the teaching of the subject can motivate the children not only to learn using the alternative to practical method but use the learned skills as adults and for live. The paper encourage the use of â€˜Alternative to Practicalâ€™ method as the latest way to go in teaching and learning of physical activities, especially sports skills, as it is effective, efficient and gives the children a kind of permanent learned benefits. The paper describes the advantage in the use of the alternative to practical method as a double barreled, since both the specialist and the trained children benefit from the development of the physical fitness build up that the method expose them to. The paper also justify the use of the method to the specialist regardless the constraints of using the method which he blamed to factors as ageing process illness etc. this tend to be natural as well. Keywords: Implications Teaching Physical Education Alternative Practical Physical Fitness